Collaboration, Negotiation, and Reflection: Meaning-making established through grounded theory - Joannidou, Shaunna; Zenios, Maria; Reynolds, Michael (Proceedings of the International Conference on Networked Learning, 2010)
This paper investigates the use of integrated technology in order to support constructivist principles and cultivate life-long learning skills. Meaning-making and creativity in learning is best achieved when activities are structured to allow students the opportunity to interact with one another through collaboration. The investigation illustrates how technology can assist students to be engaged in collaboration – an interactional meaning-making process that supports social learning, specifically in an advanced English language course, at a tertiary educational institution. Two instructors were involved and they were responsible for 80 students who were divided into four different course sections. The participants were third year Computer Science students and had already attended two previous levels of English language training. A task-based learning approach was also applied in that students were able to achieve a number of the course objectives through this activity. It was revealed that when students are able to determine the content of their learning, to establish a collaborative working environment, and to reflect as well as assess what they have as a group and/or as an individual achieved, they are better equipped with learning skills that will accompany them throughout their entire lives. Student motivation is also high due to the autonomy given when groups are able to establish a process of negotiation and meaning-making. Particularly when students are able to determine the content, collaboration and , in this study, informal assessment criteria within their social learning environment, the students not only welcomed the task, but looked forward to working towards the final goal as well as helping others along the way. A grounded theory approach was applied in order to research the personal situated view of the learners using their own words through a reflective essay and semi-structured interviews. The reflective essays were a very strong indication that the task was collaborative and supported constructivism. Through the use of grounded theory, the shared perception of the student learning environment is brought forth and documented. It brought this meaningful experience to light. Grounded Theory is a powerful tool in fleshing out what the students think, experience and discover through the learning process.